Analysis of exosomal circRNAs upon irradiation in pancreatic cancer cell repopulation - Yi-yun Chen; Ming-jie Jiang; Ling Tian (BMC, 2020)
Abstract Background Pancreatic cancer is one of the most malignant tumors. However, radiotherapy can lead to tumor recurrence, which is caused by the residual surviving cells repopulation stimulated by some molecular released from dying cells. Exosomes may mediate cell-cell communication and transfer kinds of signals from the dying cells to the surviving cells for stimulating tumor repopulation. Circular RNAs (circRNAs) may be one vital kind of exosomal cargos involving in modulating cancer cell repopulation. Methods Next generation sequencing (NGS) and bioinformatics were performed to analyze and annotate the expression and function of exosome-derived circRNAs in pancreatic cancer cells after radiation. Four circRNAs were chosen for qRT-PCR analysis to validate the sequencing results. Results In this study, 3580 circRNAs were annotated in literatures and circBase among 12,572 identified circRNAs. There were 196 filtered differentially expressed circRNAs (the up-regulation and down-regulation respectively is 182 and 14, fold change > 2, p-value < 0.05). Regulation of metabolic process and lysine degradation were the main enriched biological processes and pathway according to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Conclusions The hsa_circ_0002130-hsa_miR_4482-3p-NBN interaction network suggested potential sponging miRNA and target mRNA. Our results provided potential functions of circRNAs to explore molecular mechanisms and therapeutic targets in pancreatic cancer cell repopulation upon irradiation.